Goldfish adiponectin: (I) molecular cloning, tissue distribution, recombinant protein expression, and novel function as a satiety factor in fish model - Zheng, Yunhua; Ye, Cheng; He, Mulan; Ko, Wendy K. W.; Chan, Ying Wai; Wong, Anderson O. L. (Frontiers in Endocrinology, 2023)
Adiponectin (AdipoQ) is an adipokine involved in glucose homeostasis and lipid metabolism. In mammals, its role in appetite control is highly controversial. To shed light on the comparative aspects of AdipoQ in lower vertebrates, goldfish was used as a model to study feeding regulation by AdipoQ in fish species. As a first step, goldfish AdipoQ was cloned and found to be ubiquitously expressed at the tissue level. Using sequence alignment, protein modelling, phylogenetic analysis and comparative synteny, goldfish AdipoQ was shown to be evolutionarily related to its fish counterparts and structurally comparable to AdipoQ in higher vertebrates. In our study, recombinant goldfish AdipoQ was expressed in E. coli, purified by IMAC and confirmed to be bioactive via activation of AdipoQ receptors expressed in HepG2 cells. Feeding in goldfish revealed that plasma levels of AdipoQ and its transcript expression in the liver and brain areas involved in appetite control including the telencephalon, optic tectum and hypothalamus could be elevated by food intake. In parallel studies, IP and ICV injection of recombinant goldfish AdipoQ in goldfish were both effective in reducing foraging behaviours and food consumption. Meanwhile, transcript expression of orexigenic factors (NPY, AgRP, orexin & apelin) was suppressed with parallel rises in anorexigenic factors (POMC, CART, CCK & MCH) in the telencephalon, optic tectum and/or hypothalamus. In these brain areas, transcript signals for leptin receptor were up-regulated with concurrent drops in NPY receptor and ghrelin receptors. In the experiment with IP injection of AdipoQ, transcript expression of leptin was also elevated with a parallel drop in ghrelin mRNA in the liver. These findings suggest that AdipoQ can act as a novel satiety factor in goldfish. In this case, AdipoQ signals (both central & peripheral) can be induced by feeding and act within the brain to inhibit feeding behaviours and food intake via differential regulation of orexigenic/anorexigenic factors and their receptors. The feeding inhibition observed may also involve the hepatic action of AdipoQ by modulation of feeding regulators expressed in the liver.